Pola Komunikasi Pengasuh terhadap Anak Asuh dalam Meningkatkan Kepercayaan Diri di Panti Asuhan - Asnita, Riza; Syawaluddin, Syawaluddin (YASIN, 2023)
Children who grow up in an orphanage have the same rights as children who are in a family environment. Communication carried out by caragivers to provide motivation to foster children in terms of self-confidence. Based on this, orphanage caregivers need to carry out good communication patterns in increasing the confidence of foster children. Confidence is a very important element in everyday life. Confidence is an attitude, a feeling of confidence that exists in a person that he is capable of achieving a goal. Fpster children must ave high self-confidence to compete in terms of achievement with other children at school. The pattern of communication that must be owned by caregivers must be good so that foster children can be confident that caregivers are a place where they can tell stories and by communicating with caregivers can provide motivation for themselves.